Optimisation of rear reflectance in ultra-thin CIGS solar cells towards >20% efficiency. (April 2017) - Poncelet, Olivier; Kotipalli, Ratan; Vermang, Bart; Macleod, Angus; Francis, Laurent A.; Flandre, Denis
Highlights: Optimization of rear reflectance in CIGS solar cells. Rear reflectance up to 98% in the long wavelength 800–1100 nm range. Solar cell efficiency for thicknesses (<1 μm) were predicted using SCAPS-1D model. R b optimization to achieve J sc > 40 mA/cm 2 and η > 20% by using a 500 nm-thick CIGS. Abstract: In order to decrease their cost and the use of rare metal elements, thin film solar cell thicknesses are continuously reduced at the expense of their efficiency, due to a lack of absorption for long wavelengths. Optimisation of cells rear reflectance ( R b ) thus becomes meaningful to provide non-absorbed light a second chance to be harvested by the active cell layer. In this sense, we present a way to keep the rear reflectance in advanced Cu(In, Ga) Se2 (CIGS) cell as high as possible while keeping in mind the progress already done regarding the rear passivation techniques. We show that introducing a stack of thin Al2 O3 and aluminium between the CIGS layer and the rear molybdenum electrode increases R b up to 92% in the long wavelength 800–1100 nm range. Several other stacks, using MgF2, SiO2 or TiO2, are optimised in order to investigate the best trade-off between passivation, material consumption and performances, resulting in R b ranging from 42% (moderate case) to 99% in the best case. Those CIGS rear interface reflectance optimisations were performed by using a standard transfer matrix method (TMM) in the long wavelength range. Seven interesting stacks are then analysed for solar cell performances using SCAPS simulation software to understand the impact of rear reflectance on short circuit current density ( J sc ) and eventually on the cell efficiency ( η ), for ultra-thin CIGS absorber thicknesses (<1 μ m). Based on these results, we propose R b optimisation to achieve J sc > 40 mA/cm 2 and η > 20% with a 500 nm-thick CIGS absorber film using CIGS-Al2 O3 -Mo stack, where the Al2 O3 thickness can be chosen in between 104 and 139 nm. This way, we can ensure good rear reflectance ( R b = 65%) and reduced interface recombination while being industrially feasible with present technologies.